1999
DOI: 10.1034/j.1399-3003.1999.14c09.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung function abnormalities and respiratory muscle weakness in children with juvenile chronic arthritis

Abstract: In contrast to adult rheumatoid arthritis (RA) little is known about the prevalence, nature and cause of lung function abnormalities in children with juvenile chronic arthritis (JCA). The aim of this study was to determine whether children with polyarticular and systemic onset JCA have lung function abnormalities and if so, whether they are related to pulmonary disease, thoracic and/or muscular involvement. We determined lung function and disability in 31 children with polyarticular and systemic JCA. Respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 29 publications
2
19
1
Order By: Relevance
“…Furthermore, Pimax and Pemax were signiWcantly lower in JIA patients compared with controls. Knook et al [30] found that there was decrease in FVC, PEF, Pemax and Pimax, which were consistent with our results, but in contrast to ours, they found normal FEV1 and DLCO.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Furthermore, Pimax and Pemax were signiWcantly lower in JIA patients compared with controls. Knook et al [30] found that there was decrease in FVC, PEF, Pemax and Pimax, which were consistent with our results, but in contrast to ours, they found normal FEV1 and DLCO.…”
Section: Discussioncontrasting
confidence: 54%
“…An impairment of thoracic and/or spine mobility has been suggested to reduce thorax excursion, resulting in a tendency to develop lung function abnormalities [30][31][32]. But in our patients group, there was no impairment in thorax or spine mobility aVecting lung function.…”
Section: Discussionmentioning
confidence: 46%
“…Knook et al suggest that the reduced respiratory muscle strength in children with juvenile arthritis decreases their expiratory reserve volume, and, consequently, FVC, which indicates worsening chest wall mobility. 17 Similar to lung volumes, respiratory muscle strength was related to chest wall mobility in our study. The positive correlation between axillary cirtometry, thoracic cirtometry, and maximum inspiratory pressure (r ϭ 0.48, r ϭ 0.46, respectively) is expected, since the greater the inspiratory muscle strength, the greater the expansion of both the upper and the lower rib cage.…”
Section: Discussionsupporting
confidence: 50%
“…In the current study, the change in the Pi/PI max term was due to a decrease in PI max indicating a decrease in functional inspiratory muscle strength and a greater inspiratory demand in relation to inspiratory reserve. Atrophy and remodeling from inactivity (28); injury from overuse (29); sepsis (30); medications such as aminoglycosides, steroids, or neuromuscular blockers (31); malnutrition; and chronic illnesses (32,33) can also detrimentally affect respiratory muscle strength. In addition the degree of consciousness, respiratory drive, and lung volume can also affect measurement of PI max (34).…”
Section: Discussionmentioning
confidence: 99%